Pencegahan Stroke Pada Usia Muda Melalui Pemberdayaan Remaja Di Kelurahan Naioni - Aty, Yoani; Nurwela, Trivonia Sri; Blasius, Gadur (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The rising incidence of stroke among young people has become a significant concern in the health sector. Risk factors such as unhealthy lifestyles, poor dietary habits, lack of physical activity, and low awareness of prevention are the main causes. This programme was conducted at the Youth Posyandu in the Naioni Public Health Centre area, Kupang City, from August to October 2024. It aimed to raise youth awareness about stroke risk factors and promote healthy lifestyles. Activities included interactive health education sessions, the formation of peer educator groups, health campaigns through poster competitions, and health screenings. The programme outcomes demonstrated a significant improvement in youth knowledge. The average knowledge score increased from 35% in the pre-test to 85% in the post-test. Positive behavioural changes were recorded, with 70% of participants reducing unhealthy food consumption, 60% engaging in regular exercise, and 50% quitting smoking. Health screenings revealed that all participants had normal blood pressure and body mass index. The poster competition, themed "Healthy Lifestyle to Prevent Stroke," successfully enhanced youth creativity and understanding, with the posters displayed in public areas to maximise the dissemination of information. This programme also fostered a collective commitment between youth and the community towards stroke prevention. In conclusion, empowering young people as agents of change proved to be effective in promoting healthy lifestyles and can serve as a model for other communities in the prevention of non-communicable diseases.